Increasing Field Efficiency of Farm Machinery Using GPS - Reza Ehsani (EDIS, 2010)
AE466, a 3-page illustrated fact sheet by Reza Ehsani, shows how Global Positioning Systems data can provide very useful information about the efficiency of agricultural equipment. Published by the UF Department of Agricultural and Biological Engineering, August 2010.